Relationship between Periodontitis and Glaucoma: A Cross-Sectional Study - Soo Hwan Byun; Dae Myoung Yoo; Minwook Chang; Hyo Geun Choi; Seok Jin Hong (Journal of Ophthalmology, 2020)
The objective of this cross-sectional study was to evaluate the association between periodontitis and glaucoma. This prospective cohort study used epidemiological data from the Korean Genome and Epidemiology Study performed between 2004 and 2016. Among 173,209 participants, 9572 patients with periodontitis and 115,332 controls (nonperiodontitis) were selected. We analysed the history of glaucoma in periodontitis and control participants. The participants were interviewed regarding their history of hypertension, diabetes mellitus, hyperlipidaemia, periodontitis, glaucoma, smoking, and alcohol consumption by trained interviewers. A logistic regression model was created to analyse the odds ratio of having a history of glaucoma among patients with periodontitis. Two-tailed analyses using chi-square and independent t-tests were used for statistical analysis. The adjusted odds ratio of periodontitis as a risk factor for glaucoma was 3.44 (95% confidence interval = 2.99–3.97, p<0.001). This study demonstrated that glaucoma was associated with periodontitis.